Muscle activity of the Lumbo-pelvic-hip complex in three isometric exercises using TRX ® rip trainer™ (Actividad muscular del complejo Lumbo-Pelvis-Cadera en tres ejercicios isométricos usando TRX® rip trainer™) - Flores-Leon, Andres Felipe; Soto, Valeria; Araneda, Oscar Florencio; Guzman-Venegas, Rodrigo; Berral de la Rosa, Francisco José (Retos, 2019)
Abstract. One of the tools currently used for strengthening the lumbo-pelvic-hip complex (LPHC) is the TRX ® Rip Trainer™. This device produces asymmetric destabilizing forces by means of an elastic resistance (ER) cord. This study aimed to compare the level of muscle activity of LPHC, during the performance of three isometric exercises using TRX ® Rip Trainer™. Twenty-two healthy, physically active men (mean age 23 ± 2.35 years) were evaluated during the performance of “Drag” (anterior), "Drive" (posterior) and “Stack” (rotation) isometrically resisted exercises, performed using TRX ® Rip Trainer ™. The muscle activity of longissimus, external oblique, gluteus medius, and biceps femoris was recorded by means of surface electromyography. There were differences regarding the side of the ER location in most of the evaluated muscles (p